Leaving Poverty Behind? The Effects of Generous Income Support Paired with Activation - Simen Markussen; Knut Røed (Institute for the Study of Labor (IZA), 2014)
We evaluate a comprehensive activation program in Norway targeted at hard-to-employ social assistance claimants with reduced work capacity. The program offers a combination of tailored rehabilitation, training and job practice, and a generous, stable, and non-means-tested benefit. Its main aims are to mitigate poverty and subsequently promote self-supporting employment. Our evaluation strategy exploits a geographically staggered program introduction, and the causal effects are identified on the basis of changes in employment prospects that coincide with local program implementation in a way that correlates with the predicted probability of becoming a participant. We find that the program raised employment prospects considerably.
Keywords: C21; C26; H55; I30; J24; 330; poverty; vocational rehabilitation; social insurance; treatment effects; program evaluation